Faith-based war from 9/11 to catastrophic success in Iraq - Herbert, T. Walter (Thomas Walter), 1938- (London ; Oakville, CT : Equinox Pub., 2009)
The Bush administration was prompted to invade Iraq by a religious vision that blinded them to the realities of the struggle against terror, and propelled them into moral and political catastrophe. The propaganda campaign that promoted the war, the choice of a self-defeating Shock and Awe 'invasion, and the expanded torture program bear witness to a faith-based policy that violated democratic ideals and perverted religious truth. The White House embraced a version of Christian nationalism in which the president serves as the agent of God's of wrath to punish evildoers, in keeping with a tradition that descends from the Massachusetts Bay Puritans, who considered themselves a chosen people' occupying a promised land. As native peoples resisted Puritan encroachment at the frontiers of expansion, they were marked as devils incarnate, fit for total destruction. A modern version of this imperialist vision was invoked on 9/11, when the social and political conditions giving rise to the terrorist atrocity were forgotten, and sanctimonious wrath against evildoers ruled the White House response. At the heart of this religious mythology stands the frontier hero, 'who takes action when the not chosen' strike back against the advance guard of the chosen. 'In order to defeat the forces of evil, this cowboy champion of civilization employs savage means: he violates human law in the name of establishing God's law. The Bush administration, acting out this fantasy, claimed the right to engage in illegal surveillance and torture, and invented specious excuses for toppling a government it conceived to be evil'. The classic mythology of the American frontier allowed Christian militarists in the Religious Right of the Republican party to make common cause with broad sectors of the American public. They achieved predominant influence in the Bush White House, and in the future will seek to regain control over U.S. foreign policy. In Bush years, the government of the United States sought to play God, and this perversion of religious truth yielded abhorrent results. "Faith-Based War" discusses the analogy between the U.S. torture program and the Roman practice of crucifixion, to which Jesus fell victim, affirming that sacred authority resides in the targets of religiously-sanctioned violence, not in those who wield it. -- Publisher description.
Introduction -- Faith-based war -- Catastrophic success -- American blindspot -- Religious trauma -- America the beautiful -- Defending God's chosen -- City on a hill -- Alternative cities -- Amalek -- Limitless divine sanction -- Land of promise -- Wine of astonishment -- Rival traditions -- The fire of freedom -- The shining city as God -- Christian soldiers -- The president as mystic -- Drinking the Kool Aid -- Conquest as liberation -- Saddam as Hitler -- Unreal cities -- Avenging angel -- Saint George -- Christlike sacrifice -- The wrath of the Lamb -- Six-gun saviors -- Make-believe cowboys -- Messiahs on horseback -- Six-gun saviors in the White House -- Moral clarity and moral collapse -- Shock and awe -- Moral clarity in battle -- Dead certainty -- Shaken souls -- A theology of torture -- Advertising the dark side -- A theology of torture -- UnAmerican activities -- Coda: Hooded man.
Includes bibliographical references (pages 177-185) and index.
Print version record.
Keywords: War -- Religious aspects -- Christianity; Executive power -- United States; Iraq War, 2003-2011.; United States -- History, Military -- Religious aspects; Iraq War, 2003-; United States -- History, Military -- Religious aspects; History; Religion; Executive power; Religious aspects; War -- Religious aspects -- Christianity; United States; Christentum; Folter; Fundamentalismus; Irakkrieg; USA; HISTORY / Middle East / General; Electronic books; Military history